Identification of Geometric Concepts Contained in The Pa'binti' Weaving Crafts of The Toraja Society - Marilyn Lasarus; Ari Wibowo; Angela Angela (Universitas Muhammadiyah Enrekang, 2023)
Indonesia is a country rich in culture from various ethnic groups. Culture can be applied in schools through culture-based learning. Toraja is one of the tribes in Indonesia that has a variety of cultures. Woven craft is one of the cultures occupied by the Toraja people since ancient times until now. Weaving pa'binti' is a woven craft of the Toraja people, especially the Sa'dan area, which is made from yarn. In pa'binti weaving, there are mathematical concepts in it in the form of flat shapes. The purpose of this study was to determine the geometric concepts contained in the pa'binti woven woven craft of the Toraja people. This study uses a qualitative descriptive method to study and understand more deeply about ethnomatics in the woven weaving craft of the Toraja people. The research location is in the North Toraja area, namely in Lembang Sa'dan Ulusalu, Sa'dan sub-district. The results of this study are that there is a geometric concept in the pa'binti woven woven craft of the Toraja people where the geometric concepts contained in the pa'binti woven woven craft include; flat triangle, rhombus, square, and parallelogram.